KONDISI SOSIAL EKONOMI PETANI CENGKEH DI NAGARI SANIANGBAKA KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Syah, Zikry; Surtani, Surtani (JURNAL BUANA, 2024)
This study aims to describe the Socio-Economic Condition of Clove Farmers in Nagari Saniangbaka, X Koto Singkarak District, Solok Regency. This type of research uses quantitative descriptive using purposive sampling technique. The sample of research respondents was calculated using the Slovin formula with an error rate of 10%, so that the sample of respondents was 90 clove farmers. The results of the study can be concluded that: The Saniangbaka community works as main and secondary clove farmers. The education level of the main clove farmers is elementary school (SD) and the secondary clove farmer education is high school or equivalent (SMA). The health condition is quite good, judging from the time of illness in the last 6 months, only 38.9% felt sick 4-6 times. The income from clove crop per month is less than Rp. 1,000,000, with a percentage of 86.7%. The area of ​​land owned by the main clove farmers is larger than that of the secondary clove farmers. The amount of clove production obtained is less than 10 kg/month with a percentage of 81.1%.